Human pegivirus persistence in human blood virome after allogeneic haematopoietic stem-cell transplantation. (February 2019) - Vu, D.-L.; Cordey, S.; Simonetta, F.; Brito, F.; Docquier, M.; Turin, L.; van Delden, C.; Boely, E.; Dantin, C.; Pradier, A.; Roosnek, E.; Chalandon, Y.; et al.
Abstract: Objectives: Because commensal viruses are defined by the immunologic tolerance afforded to them, any immunomodulation, such as is received during haematopoietic stem-cell transplantation, may shift the demarcation between innocuous viral resident and disease-causing pathogen. Methods: We analysed by deep-sequencing the plasma virome of 40 allogeneic haematopoietic stem-cell transplantation patients 1 month after transplantation. Because human pegivirus (HPgV) was highly prevalent, we performed a 1-year screening of 122 plasma samples by specific real-time reverse transcription PCR assay. We used the log-rank test and the Gray test to assess association with outcomes, and the Mann-Whitney test and multivariable linear regression model to assess association with T-cell reconstitution. Results: Polyomaviruses (PyV) (20/40 patients), anelloviruses (16/40), pegiviruses (14/40) and herpesviruses (14/40) were most frequently identified, including ten cytomegalovirus; three Epstein-Barr virus; two herpes simplex virus type 1; one human herpesvirus 6b and one human herpesvirus 7; 18 Merkel cell–PyV; two BK-PyV; three PyV-6; and one JC-PyV. Papillomavirus and adenovirus were identified in 11 and two patients, respectively. The HPgV specific real-time reverse transcription PCR screening identified 51 of 122 positive samples, high virus loads and persistent infections up to 1 year after transplantation. Comparison between patients with or without HPgV infection at time of transplantation did not reveal a significant difference in infections, engraftment, survival, graft vs. host disease, relapse or immune reconstitution. Conclusions: The blood virome after allogeneic haematopoietic stem-cell transplantation includes several DNA viruses, notably herpesviruses and PyV. Among RNA viruses, HPgV is highly prevalent and persists for several months, and it thus may deserve special attention in further research on immune reconstitution.